2021
DOI: 10.3390/polym13091455
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of Sensors for Military Monitoring Applications

Abstract: The US Department of Defense (DoD) realizes the many uses of additive manufacturing (AM) as it has become a common fabrication technique for an extensive range of engineering components in several industrial sectors. 3D Printed (3DP) sensor technology offers high-performance features as a way to track individual warfighters on the battlefield, offering protection from threats such as weaponized toxins, bacteria or virus, with real-time monitoring of physiological events, advanced diagnostics, and connected fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…[ 221 ] Self‐assembling and self‐repairing 4DPed objects could be utilized for developing military equipment. [ 222 ]…”
Section: Applications Of 4d Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 221 ] Self‐assembling and self‐repairing 4DPed objects could be utilized for developing military equipment. [ 222 ]…”
Section: Applications Of 4d Printingmentioning
confidence: 99%
“…[221] Self-assembling and self-repairing 4DPed objects could be utilized for developing military equipment. [222] Lately, there has been a growing interest in the implementation of 4DP technology in textiles industries. For example, there is a need to use large membranes in textiles for different purposes such as alleviating the physiological burden, minimal decay of membrane, limited effect of liquid, biological or chemical agents, and dirt's free textile surface.…”
Section: Other Engineering Applicationsmentioning
confidence: 99%
“…Rapid prototyping technologies, such as additive manufacturing (AM), allow the fabrication of assembly parts of such systems [19][20][21]. Numerous studies have shown the possibilities of rapid prototyping technologies and their application [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, polymer materials for 3D printing are currently being produced with a wider range of properties [2]. Today, AM is being used to produce materials for different applications, namely, automotive [3] electronics [4] robots [3], construction [5], apparel [6], medicine [7], dentistry [8] aerospace [9], military [10], and others. However, in these practical applications, the parts manufactured by 3D-printing processes must withstand different quantities of mechanical stress imposed by the environment.…”
Section: Introductionmentioning
confidence: 99%